On periodic boundary value problem for a differential equation of n-th order - Dłotko, Tadeusz (Annales Mathematicae Silesianae, 1991)
The problem (1) is investigated. New sufficient conditions are derived for the existence of at least one solution in the space C[0,w](n-1). The proof is based on the topological degree method in the Banach space of solutions.